Odpowiedź:
a)
4(6x-1)=8(x-5)
24x-4=8x-40
16x=-36
x=-36/16=-2 i 1/4
b)
9(4x-6)<12(x-4)
36x-54<12x-48
24x<6
x<6/24
x<1/4
x€(-∞,1/4)
c)
5(x-6)≥8(2x+4)
5x-30≥16x+32
-11x≥62
x≤-62/11
x≤-5 i 7/11
x€(-∞,-5i7/11>
d)
[6x-3]/2=8. /×2
6x-3=16
6x=19
x=19/6=3i1/6
e)
[9x-4]/6=2. ×6
9x-4=12
9x=16
x=16/9=1i7/9
f)
[5-4x]/4=-2. /×4
5-4x=-8
-4x=-13
x=13/4=3i1/4
g)
[6x+3]/2=4-3x. /×2
6x+3=8-6x
12x=5
x=5/12
h)
[5x+3]/2 + [4x-6]/2=4. /×2
5x+3+4x-6=8
9x=11
x=11/9=1i2/9
i)
[6x-8]/3+[4x-4]/3=6 /×3
6x-8+4x-4=18
10x=30
x=3
j)
(x-1)(x+4)<(x-5)(x+8)
x²+4x-x-4<x²+8x-5x-40
0<-36
k)
(x+2)(x-6)≥(x+4)(x-7)
x²-6x+2x-12≥x²-7x+4x-28
x≥-16
x€<-16,+∞)
l)
-1/2x<6. /×(-2)
x>-12
x€(-12,+∞)
m)
6x≥1/4. /×1/6
x≥1/24
x€<1/24,+∞)
n)
2 1/3x=5
7/3x=5. /×(3/7)
x=15/7=2 i 1/7
o)
6 1/2x=2 1/2
13/2x=5/2. /×2/13
x=5/13